An Angiopep2-PAPTP Construct Overcomes the Blood-Brain Barrier. New Perspectives against Brain Tumors - Sofia Parrasia; Andrea Rossa; Tatiana Varanita; Vanessa Checchetto; Riccardo De Lorenzi; Mario Zoratti; Cristina Paradisi; Paolo Ruzza; Andrea Mattarei; Ildikò Szabò; Lucia Biasutto (MDPI AG, 2021)
A developing family of chemotherapeutics-derived from 5-(4-phenoxybutoxy)psoralen (PAP-1)-target mitochondrial potassium channel mtKv1.3 to selectively induce oxidative stress and death of diseased cells. The key to their effectiveness is the presence of a positively charged triphenylphosphonium group which drives their accumulation in the organelles. These compounds have proven their preclinical worth in murine models of cancers such as melanoma and pancreatic adenocarcinoma. In in vitro experiments they also efficiently killed glioblastoma cells, but in vivo they were powerless against orthotopic glioma because they were completely unable to overcome the blood-brain barrier. In an effort to improve brain delivery we have now coupled one of these promising compounds, PAPTP, to well-known cell-penetrating and brain-targeting peptides TAT48-61 and Angiopep-2. Coupling has been obtained by linking one of the phenyl groups of the triphenylphosphonium to the first amino acid of the peptide via a reversible carbamate ester bond. Both TAT48-61 and Angiopep-2 allowed the delivery of 0.3-0.4 nmoles of construct per gram of brain tissue upon intravenous (i.v.) injection of 5 µmoles/kg bw to mice. This is the first evidence of PAPTP delivery to the brain; the chemical strategy described here opens the possibility to conjugate PAPTP to small peptides in order to fine-tune tissue distribution of this interesting compound.